Dynamics of some indicators of morphology and biochemistry of the blood of rabbits in conditions of stress and immune correction therapy with «Ronkoleukin®» and «Gamavit» preparations - T Y Vishnevskaya; L L Abramova (RUDN Journal of Agronomy and Animal Industries, 2012)
The paper presents an analysis of some indicators of the morphology and biochemistry of the blood of rabbits in conditions of stress and immune correction therapy Ronkoleukin® and Gamavit. The data on indicators of blood hemoglobin concentration, erythrocyte count, total and agranular leukocytes, glucose content. Revealed a positive effect on the body of stress animals immunomodulators, more Gamavita.